Analisis Perubahan Ruang Terbuka Hijau dengan Citra Resolusi Tinggi di Kota Depok - Gunadi, Syahbani Putra; Syartinilia; Pravitasari, Andrea Emma (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2025)
The massive changes in land cover in Depok City, which serves as a buffer zone for the capital city of Jakarta, have led to a decrease in Green Open Space (GOS) due to the high demand for land for development. To monitor changes in GOS land cover and obtain accurate analysis results, appropriate tools, data, and methods are required. This study employed remote sensing and GIS techniques to assess GOS changes in Depok City between 2013 and 2021. The tools used included ArcGIS 10.8, Google Earth Pro, and a set of computers. The study utilized high-resolution Spot 6 and 7 satellite imagery with analysis conducted using the supervised classification method and the maximum likelihood algorithm. The results of this study produced land cover maps with very high accuracy, where the overall accuracy and kappa coefficient were 96% and 93% in 2013, and 97% and 92% in 2021, respectively. The classification results revealed a significant decrease in GOS over the past eight years, with a reduction of 20.2% of the total area, resulting in GOS coverage of only 31.3% or 6,239 ha in 2021. Most of the GOS reduction was caused by the expansion of built-up areas, which increased by 4,857 ha. Other changes were observed in water bodies 99 ha and open land 73 ha. The GOS analysis in Depok City using the supervised classification method on high-resolution Spot imagery proved to be highly accurate compared to previous studies that used Landsat 8 OLI imagery with the NDVI method.